FABRICATION AND CHARACTERIZATION OF SENSITIZED SOLAR CELLS BASED ON TiO2 MODIFIED WITH NiO NANOPARTICLES - Galicia Toralva, María (2016)
Sensitized solar cells working electrodes of titania (TiO2) nanoparticles were modified with nickel oxide (NiO), which were synthesized from nickel chloride (NiCl2.6H2O). The deposit of the working electrode was performed by Doctor. Blade technique and the sensitization process was performed using commercial dye: Di-tetrabutylammonium cis-bis (isothiocyanato) bis (2,2'-bipyridyl-4,4 '-dicarboxylato) ruthenium (II), also known as N719. The structural and morphological characterization of the working electrodes was performed by X-ray diffraction and scanning electron microscopy, respectively. The photoelectrochemical characterization of the working electrodes and solar cells was performed by measuring the Incident Photon to Current Efficiency (IPCE) and the current-voltage, respectively. Ni concentration in the TiO2 powder was 125 ppm as determinated by atomic absorption. Efficiency measurements as solar cell, for TiO2 modified with NiO (TiO2∙NiO) reached a value of 3.7%, greater than that obtained for solar cells base only on TiO2, which reached an efficiency of 1, 4 %.